Multifunctional liquid crystal nanoparticles for cancer therapy - Mehata A.K.; Dehari D.; Gupta A.; Rabin D.C.; Miya A. (My University, 2025)
Cancer is the second foremost reason for worldwide death, affecting every country of the globe. However, 70% of cancer-related death was reported from low-and middle-income na-tions. Delay in the detection and intervention of therapeutic agents in cancer patients also promoted a cancer-related mortality index. Currently, numerous nanomedicines are under development for ad-vancing tumor diagnosis and therapeutic capability. Recently, liquid crystalline nanoparticles (LC-NPs) have emerged as an attractive drug delivery system for both intravenous and non-intravenous applications. The widely explored LCNPs for cancer therapy include cubosomes and hexosomes. They have significant advantages over other drug delivery system, which includes, high internal surface area, unique solubilization properties and sustained release of entrapped drug molecules and co-loading of imaging and therapeutic agents in a single system. In this review, we have brief-ly discussed the advantages of LCNPs, preparation methods, and their multifunctional role in treat-ing various cancers. © 2021 Bentham Science Publishers.